Optical and tribo-mechanical characterization in metal-ceramic multilayers coatings (2020)
Laboratory scale studies of tribological properties of nitride coatings are useful in predicting their protective wear behavior in cutting toolsfor industrial-scale applications. The main aim of this research is to determine optical and tribo-mechanical properties in multilayer coatingsof metal-ceramic assigned as coatings A and B. These coatings were deposited by DC magnetron sputtering on carbon steel AISI 1060using buffer adhesion layers of W, Ti/W/WN and TiN/TiN respectively. For to determine molecules, interactions of materials were analyzedthrough of Raman and FTR spectroscopies. The nanohardness, tribological and adhesion behavior were studied by nanoindentation, pinon disk and a tribometer. The hardness and behavior tribological, were obtained by Nano-indentation, pin on disk, and scratch test using atribometer. FTIR and Raman analysis shown the formation of Ti metallic ion and WO3mainly in both coatings. The hardness of coatingsshown a slight improvement compared with the substrate. However, for industrial applications this property should be increase. The behaviorof COF does not present improvement. The mass loss and wear rate were high signiﬁcantly due to the formation of cracks on surface coatings.Scratch analysis, it found three wear mechanics determined by the presence of irregular borders with sharp shadow, semicircle detachmentin coatings and coatings detachment in the central track as the load increased